Nano material and preparation method and application thereof

By doping ZnO nanoparticles with ionic stabilizers and silicone stabilizers, the problem of poor stability of ZnO nanoparticles is solved, achieving higher stability and longer ink storage time, which is suitable for electronic transmission materials and ink industries. .

CN119330392APending Publication Date: 2025-01-21GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310901422.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

ZnO nanoparticles have poor stability and are prone to agglomeration, affecting the performance of electron transport materials.

Method used

By doping stabilizers in ZnO nanoparticles, including ionic stabilizers and silicone stabilizers, the reaction barrier of the nanomaterials is increased, the reaction time is prolonged or the reaction temperature is increased to enhance its stability.

Benefits of technology

It improves the stability of ZnO nanomaterials, slows down particle agglomeration, prolongs the storage time of ink, reduces the frequency of ink replacement, and is beneficial to industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330392A_ABST
    Figure CN119330392A_ABST
Patent Text Reader

Abstract

The invention relates to a nano material as well as a preparation method and application thereof. The nanometer material comprises ZnO nanometer particles and a stabilizing agent doped in the ZnO nanometer particles; the stabilizer comprises at least one of an ion stabilizer and an organic silicon stabilizer. The stabilizer has relatively stable chemical properties, can improve the reaction barrier of a reaction system in the ZnO preparation process, obviously improves the reaction conditions such as reaction time or reaction temperature and the like under the condition of generating nano materials with the same particle size, and can improve the stability of the nano materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electron transport materials, and in particular to a nano material and a preparation method and application thereof. Background Art

[0002] OLED (organic light-emitting diode) and QLED (quantum dot light-emitting diode) are generally composed of multiple functional layers such as cathode, electron injection layer, electron transport layer, light-emitting layer, hole injection layer, hole transport layer, anode, etc. The functional layer can be prepared by solution process to greatly improve the material utilization rate and realize large-scale production, so it has become a research hotspot for low-cost, large-size electronic light-emitting device panel production process.

[0003] For inorganic electron transport materials, ZnO nanoparticles are often used. However, ZnO nanoparticles are prone to agglomeration and have poor stability. Summary of the invention

[0004] Based on this, it is necessary to provide a nanomaterial and a preparation method and application thereof.

[0005] In a first aspect, the present application provides a nanomaterial, comprising ZnO nanoparticles and a stabilizer doped in the ZnO nanoparticles, wherein the stabilizer comprises at least one of an ion stabilizer and an organosilicon stabilizer.

[0006] In one embodiment, the molar ratio of the ZnO nanoparticles to the stabilizer is (0.1-100):1; and / or

[0007] The molecular weight of the organosilicon stabilizer is less than 10,000.

[0008] In one embodiment, the ion stabilizer includes at least one of fluoride ions, lithium ions, boron ions, nickel ions, zirconium ions, titanium ions, cuprous ions and copper ions; and / or

[0009] The organosilicon stabilizer is selected from at least one of the compounds represented by formula (I) to formula (IV):

[0010]

[0011] R1-R4 are independently selected from C1-C 10 alkyl;

[0012] R5-R 10 independently selected from H atoms, phenyl groups, C1-C 10 Alkyl, C1-C 10 Alkoxy;

[0013] R 11 -R 13 Independently selected from C1-C10 Alkyl, phenyl, trimethylsilyl; R 14 Selected from halogen atoms, hydroxyl groups, C1-C 10 Alkyl, imidazole, trimethylsilyl, -A1-COO-A2, wherein A1 and A2 are independently selected from C1-C 10 alkyl;

[0014] R 15 -R 20 Independently C1-C 10 alkyl;

[0015] R 21 Independently selected from C1-C 10 alkyl.

[0016] In one embodiment, the organosilicon stabilizer is selected from at least one of methyl orthosilicate, tetraacetic silicon, ethyl silicate 40, hexamethoxydisiloxane, hexaphenyldisiloxane, hexamethyldisiloxane, pentamethyldisiloxane, tri(trimethylsilyl)chlorosilane, tetra(trimethylsilyl)silane, trimethylsilylimidazole, ethyl trimethylsilyl acetate, 2-(trimethylsilyl)ethanol, triphenylsilanol and hexamethyldisiloxane urea.

[0017] In one embodiment, the stabilizer comprises an ionic stabilizer and an organosilicon stabilizer; and / or

[0018] The molar ratio of the ionic stabilizer to the organosilicon stabilizer is (1-5):(1-5).

[0019] In a second aspect, the present application provides a method for preparing a nanomaterial, comprising the following steps:

[0020] Providing a Zn source precursor solution, an alkali source precursor solution and a stabilizer solution;

[0021] The Zn source precursor solution, the alkali source precursor solution and the stabilizer solution are mixed and reacted to obtain the nanomaterial;

[0022] The stabilizer solution includes at least one of an ionic stabilizer precursor and an organosilicon stabilizer.

[0023] In one embodiment, the Zn source precursor solution includes a Zn source precursor, and the alkali source precursor solution includes an alkali source precursor;

[0024] The molar ratio of the Zn source precursor to the stabilizer is (0.1-100):1, and the molar ratio of the Zn source precursor to the alkali source precursor is (0.1-10):1; and / or,

[0025] The ion stabilizer precursor includes at least one of a fluoride salt, a lithium salt, a boron salt, a nickel salt, a zirconium salt, a titanium salt and a copper salt; and / or,

[0026] The molecular weight of the organosilicon stabilizer is less than 10,000.

[0027] In one embodiment, the ion stabilizer precursor meets at least one of the following characteristics:

[0028] (1) The fluoride salt is at least one selected from ammonium fluoride, aluminum fluoride, strontium fluoride and zirconium fluoride;

[0029] (2) The lithium salt is at least one selected from lithium chloride, lithium fluoride, lithium acetate, lithium phosphate, lithium methoxide and lithium benzoate;

[0030] (3) The boron salt is selected from at least one of boron chloride, boron fluoride and boron tribromide;

[0031] (4) The nickel salt is at least one selected from nickel chloride, nickel fluoride, nickel bromide and nickel iodide;

[0032] (5) The zirconium salt is at least one selected from zirconium chloride, zirconium boride, zirconium bromide and zirconium acetate;

[0033] (6) The titanium salt is at least one selected from titanium chloride, titanium bromide, titanium tetrafluoride and titanium n-propoxide;

[0034] (7) The copper salt is selected from at least one of cuprous acetate, cuprous sulfide, cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride and cupric fluoride.

[0035] In one embodiment, the Zn source is selected from at least one of zinc carboxylate, zinc alcohol, zinc amino acid, zinc chloride, zinc nitrate, zinc bromide, zinc borate and basic zinc carbonate.

[0036] In one embodiment, the alkaline source precursor is selected from at least one of alkali metal hydroxides, alkaline earth metal hydroxides, and Lewis bases.

[0037] In one embodiment, the alkali metal hydroxide is selected from at least one of lithium hydroxide and sodium hydroxide; the alkaline earth metal hydroxide is barium hydroxide; the Lewis base is, for example, at least one of ammonia water, tetramethylammonium hydroxide, lithium acetate, sodium acetate, sodium methoxide, potassium tert-butoxide, alkyl lithium, and Grignard reagent.

[0038] In one embodiment, the Zn source precursor solution also includes a first solvent, the alkali source precursor solution also includes a second solvent, and the stabilizer solution also includes a third solvent, and the first solvent, the second solvent and the third solvent are independently selected from at least one of DMSO, DMF, NMF, NMP, methanol, ethanol, ethylene glycol monomethyl ether, glycerol, water, octadecene and n-octane.

[0039] In one embodiment, the reaction is carried out at -20°C to 130°C, and the reaction time is 10 min to 960 h; and / or the reaction time is 100 h to 200 h.

[0040] In a third aspect, the present application provides an ink comprising an organic solvent and the nanomaterial described in any one of the above embodiments or the nanomaterial prepared by the preparation method described in any one of the above embodiments.

[0041] In one embodiment, the organic solvent includes: at least one of a polar solvent, a saturated hydrocarbon solvent, an unsaturated hydrocarbon solvent, an alcohol solvent, an ether solvent, and a ketone solvent; and / or

[0042] The organic solvent includes DMSO, DMF, NMF, NMP, methanol, ethanol, ethylene glycol, propanol, pentanol, hexanol, cyclohexanol, n-butanol, benzyl alcohol, phenylethanol glycol monomethyl ether, glycerol, octadecene and n-octane; and / or

[0043] The mass fraction of the nano material is 0.1%-20.0%; the mass fraction of the organic solvent is 80.0%-99.9%.

[0044] In a fourth aspect, the present application provides a light-emitting device, comprising a first electrode layer, an electron transport layer, a light-emitting layer and a second electrode layer stacked in sequence; the electron transport layer comprises the nanomaterial described in any of the above embodiments or the nanomaterial prepared by the preparation method described in any of the above embodiments, or the electron transport layer is prepared by the ink described in any of the above embodiments.

[0045] In one embodiment, the materials of the first electrode layer and the second electrode layer are independently selected from at least one of metals, metal oxides and conductive carbon materials.

[0046] In one embodiment, the material of the light-emitting layer is a quantum dot light-emitting material or an organic light-emitting material.

[0047] In a fifth aspect, the present application provides a display device, comprising the light-emitting device described in any of the above embodiments.

[0048] Compared with the traditional scheme, the above-mentioned nanomaterials and preparation methods thereof, electron transport layers, light-emitting devices, and display devices have the following beneficial effects:

[0049] The above-mentioned nanomaterial contains a stabilizer doped in the ZnO nanoparticles. Its relatively stable chemical properties can increase the reaction barrier of the reaction system. When generating nanomaterials with the same particle size, the reaction conditions such as reaction time or reaction temperature are significantly improved, which can improve its stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 FIG. 1 is a schematic structural diagram of a light emitting device according to an embodiment of the present invention.

[0051] Description of reference numerals:

[0052] 100, light-emitting device; 110, first electrode layer; 120, electron transport layer; 130, light-emitting layer; 140, second electrode layer; 150, electron injection layer; 160, hole transport layer; 170, hole injection layer; 180, substrate. DETAILED DESCRIPTION

[0053] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0054] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0055] In the description of the present invention, it should be understood that the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number or order of the indicated technical features.

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The reagents and materials mentioned herein, unless otherwise specified, can be obtained by commercial means or by synthesis of existing methods. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0057] Research has found that the stability problem of ZnO nanoparticles is due to the low reaction barrier of zinc oxide, which has the characteristics of nucleation and growth at room temperature. Although this makes the reaction conditions simple and the reaction process highly controllable during synthesis, it also makes the prepared zinc oxide continue to react at room temperature, resulting in poor stability of ZnO nanoparticles. The purpose of doping ZnO-based nanoparticles with metal cations such as aluminum, gallium, and magnesium is to adjust the surface defects, energy levels, positive adsorption layers, surface ligand types and contents of the nanoparticles. However, research has found that these metal cations that can be doped into ZnO-based nanoparticles at room temperature have limited improvement on their stability.

[0058] To this end, the present invention provides a nanomaterial. The nanomaterial of one embodiment includes ZnO nanoparticles and a stabilizer doped in the ZnO nanoparticles. The stabilizer includes at least one of an ion stabilizer and an organosilicon stabilizer. The ion stabilizer includes at least one of fluoride ions, lithium ions, boron ions, nickel ions, zirconium ions, titanium ions, cuprous ions and cupric ions, and the molecular weight of the organosilicon stabilizer is less than 10,000, for example, a molecular weight of 100-1000.

[0059] The nanomaterial contains a stabilizer doped in ZnO nanoparticles, and the stabilizer includes at least one of fluorine ions, lithium ions, boron ions, nickel ions, zirconium ions, titanium ions, cuprous ions, cupric ions and silicone. Its relatively stable chemical properties can increase the reaction barrier of the reaction system during the ZnO preparation process. When generating ZnO-based nanomaterials with the same particle size, the reaction conditions such as reaction time or reaction temperature are significantly improved, which can improve its stability.

[0060] The reaction barrier is the energy difference that needs to be overcome to obtain the product from the reactants in a chemical reaction. When the reaction barrier is higher, the energy required for the reaction is higher, the reaction rate is slower, the more difficult it is to obtain the product, and the proportion of the product obtained in the same reaction time is lower. Increasing the reaction temperature and adding a forward catalyst are all helpful in overcoming the reaction barrier. Correspondingly, adding a reverse catalyst that can inhibit the production of the product to the reaction system can increase the reaction barrier.

[0061] Adding the above-mentioned stabilizers such as fluoride ions, lithium ions, boron ions, nickel ions, zirconium ions, titanium ions, cuprous ions, cupric ions and small molecule organic silicon into the reaction system can play the role of reverse catalyst and increase the reaction barrier for generating ZnO-based nanomaterials.

[0062] In addition, the stabilizer can modify the surface of ZnO nanoparticles and adjust their band gap, thereby inhibiting the aggregation and degradation of ZnO-based nanomaterials during their use.

[0063] Compared with traditional ZnO nanoparticles, the above-mentioned ZnO-based nanomaterials have better stability. As ink solutes, they can extend the storage time of ink in the printer, reduce the frequency of ink replacement, and are beneficial to industrial production.

[0064] Optionally, the molar ratio of ZnO nanoparticles to stabilizer is (0.1-100): 1. Further, the molar ratio of ZnO nanoparticles to stabilizer is (1-100): 1. Further, the molar ratio of ZnO nanoparticles to stabilizer is (10-50): 1. Within this ratio range, the overall stability of ZnO nanoparticles and stabilizer can be improved, and the conductivity of nanomaterials can be guaranteed, so that the light-emitting device containing nanomaterials maintains a high current efficiency.

[0065] Optionally, the organosilicon is selected from at least one of the compounds represented by formula (I) to formula (V):

[0066]

[0067] R1-R4 are independently selected from C1-C 10 alkyl.

[0068] R5-R 10 independently selected from H atoms, phenyl groups, C1-C 10 Alkyl, C1-C 10 Alkoxy.

[0069] R 11 -R 13 Independently selected from C1-C 10 Alkyl, phenyl, trimethylsilyl; R 14 Selected from halogen atoms, hydroxyl groups, C1-C 10 Alkyl, imidazole, trimethylsilyl, -A1-COO-A2, wherein A1 and A2 are independently selected from C1-C 10 alkyl.

[0070] R 15 -R 20 Independently C1-C 10 alkyl.

[0071] R 21Independently selected from C1-C 10 alkyl.

[0072] Furthermore, the organosilicon is selected from at least one of methyl orthosilicate, tetraacetic silicon, ethyl silicate 40, hexamethoxydisiloxane, hexaphenyldisiloxane, hexamethyldisiloxane, pentamethyldisiloxane, tri(trimethylsilyl)chlorosilane, tetra(trimethylsilyl)silane, trimethylsilylimidazole, ethyl trimethylsilyl acetate, 2-(trimethylsilyl)ethanol, hexamethyldisiloxane urea, and triphenylsilanol.

[0073] Optionally, the stabilizer includes an ionic stabilizer and an organosilicon stabilizer; and / or the molar ratio of the ionic stabilizer to the organosilicon stabilizer is (1-5):(1-5). Further, the molar ratio of the ionic stabilizer to the organosilicon stabilizer is (2-3):2. By combining the ionic stabilizer and the organosilicon stabilizer, the reaction barrier of the ZnO nanoparticles can be increased, and the stability of the nanomaterial can be further improved.

[0074] The present invention also provides a method for preparing any of the above-mentioned nanomaterials.

[0075] The method for preparing the nanomaterial of one embodiment comprises the following steps:

[0076] Providing a Zn source precursor solution, an alkali source precursor solution and a stabilizer solution;

[0077] The Zn source precursor solution, the alkali source precursor solution and the stabilizer solution are mixed and reacted to obtain the nanomaterial;

[0078] The stabilizer solution includes at least one of an ionic stabilizer precursor and an organosilicon stabilizer.

[0079] Among them, the ion stabilizer precursor includes at least one of fluoride salt, lithium salt, boron salt, nickel salt, zirconium salt, titanium salt and copper salt; the molecular weight of the silicone stabilizer is less than 10,000.

[0080] The above-mentioned nanomaterials use organic silicon, fluoride salts, lithium salts, boron salts, nickel salts, zirconium salts, titanium salts, copper salts to react with Zn source precursors and alkali source precursors, which can increase the reaction barrier of the reactants. The nanomaterials prepared by crossing the higher reaction barrier during synthesis continue to react at a slower rate at room temperature than nanomaterials synthesized by traditional methods, which can slow down particle agglomeration and thus improve their stability.

[0081] Optionally, the Zn source precursor solution includes a Zn source precursor, and the alkali source precursor solution includes an alkali source precursor; the molar ratio of the Zn source precursor to the stabilizer is (0.1-100): 1. Further, the molar ratio of the Zn source precursor to the stabilizer is (1-100): 1. Further, the molar ratio of the Zn source precursor to the stabilizer is (10-50): 1.

[0082] Optionally, the molar ratio of the Zn source precursor to the alkali source precursor is (0.1-10) : 1. Further, the molar ratio of the Zn source precursor to the alkali source precursor is (1-10) : 1. Further, the molar ratio of the Zn source precursor to the alkali source precursor is (1-5) : 1.

[0083] Optionally, the temperature of the above reaction is -20°C to 130°C, for example -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 120°C, 130°C, etc. Optionally, the time of the above reaction is 10min to 960h, for example 15min, 30min, 1h, 2h, 5h, 10h, 20h, 40h, 60h, 80h, 100h, 120h, 150h, 200h, 300h, 400h, etc. In some of these examples, the temperature of the reaction is -20°C to 80°C, and the time is 15min to 200h. In some of these examples, the temperature of the reaction is 20°C to 80°C, and the time is 1h to 200h.

[0084] Optionally, the reaction time is 10 hours to 200 hours. Optionally, the reaction time is 100 hours to 200 hours. The reaction is carried out for a longer time, which can reduce the free ZnO and form a more compact lattice structure, which is more difficult to dissociate and agglomerate, so that the nanomaterial has better stability, thereby suppressing the possibility of changes after storage at room temperature and film formation in the device.

[0085] Furthermore, the reaction conditions may include at least one of ultrasonic treatment, microwave treatment, mechanical stirring, and magnetic stirring.

[0086] The parameters of the ultrasonic treatment include: a frequency range of 15KHz to 60KHz, an ultrasonic time of 10min to 40 days, and an ultrasonic power of 50W to 2200W.

[0087] The parameters of the microwave treatment include: a frequency range of 300 MHz to 100 GHz, a microwave time of 10 minutes to 40 days, and a power ranging from 50 W to 2200 W.

[0088] The rotation speed of the mechanical stirring and the magnetic stirring is in the range of 100 rpm to 5000 rpm.

[0089] Optionally, the fluoride salt is at least one of ammonium fluoride, aluminum fluoride, strontium fluoride, and zirconium fluoride.

[0090] Optionally, the lithium salt is at least one of lithium chloride, lithium fluoride, lithium acetate, lithium phosphate, lithium methoxide, and lithium benzoate.

[0091] Optionally, the boron salt is at least one of boron chloride, boron fluoride, and boron tribromide.

[0092] Optionally, the nickel salt is at least one of nickel chloride, nickel fluoride, nickel bromide and nickel iodide.

[0093] Optionally, the zirconium salt is at least one of zirconium chloride, zirconium boride, zirconium bromide and zirconium acetate.

[0094] Optionally, the titanium salt is at least one of titanium chloride, titanium bromide, titanium tetrafluoride, and titanium n-propoxide.

[0095] Optionally, the monovalent copper salt is at least one of cuprous acetate, cuprous sulfide, cuprous chloride, cuprous bromide, and cuprous iodide.

[0096] Optionally, the divalent copper salt is at least one of copper chloride and copper fluoride.

[0097] Optionally, the Zn source may be an organic zinc salt or an inorganic zinc salt.

[0098] Examples of organic zinc salts include zinc carboxylates, zinc alcoholates, and zinc amino acids. Examples of zinc carboxylates include zinc formate, zinc acetate, zinc propionate, zinc acetate dihydrate, zinc formate dihydrate, etc. Organic zinc alcoholates include zinc methoxide, zinc ethoxide, zinc isopropoxide, etc. Amino acid zinc includes zinc glycinate, zinc alanine, etc. Examples of inorganic zinc salts include zinc chloride, zinc nitrate, zinc bromide, zinc borate, basic zinc carbonate, etc.

[0099] The above salts may be hydrates or non-hydrates. For example, copper fluoride includes anhydrous copper fluoride and hydrated copper fluoride, and zinc carboxylates include anhydrous zinc carboxylates and hydrated zinc carboxylates. Optionally, the alkali source precursor is selected from at least one of alkali metal hydroxides, alkaline earth metal hydroxides, and Lewis bases.

[0100] Examples of alkali metal hydroxides include lithium hydroxide and sodium hydroxide. Examples of alkaline earth metal hydroxides include barium hydroxide. Examples of Lewis bases include aqueous ammonia and organic bases, and examples of organic bases include TMAH (tetramethylammonium hydroxide), lithium acetate, sodium acetate, sodium methoxide, potassium tert-butoxide, alkyl lithium reagents, and Grignard reagents.

[0101] Optionally, the solvent may be at least one of an aprotic polar solvent, a protic solvent, and a non-polar solvent.

[0102] Examples of aprotic polar solvents include DMSO (dimethyl sulfoxide), DMF (N,N-dimethylformamide, NMF (N-methylformamide), NMP (N-methylpyrrolidone), etc. Examples of protic solvents include methanol, ethanol, ethylene glycol monomethyl ether, glycerol, water, etc. Examples of non-polar solvents include octadecene, n-octane, etc.

[0103] Furthermore, the present invention also provides a nanomaterial prepared by the above preparation method.

[0104] Furthermore, the present invention also provides an ink comprising an organic solvent and the nanomaterial described in any one of the above embodiments or the nanomaterial prepared by the preparation method described in any one of the above embodiments.

[0105] In one embodiment, the organic solvent includes: at least one of polar solvents, saturated hydrocarbon solvents, unsaturated hydrocarbon solvents, alcohol solvents, ether solvents, ketone solvents, and one or more of their derivatives, including but not limited to DMSO, DMF, NMF, NMP, methanol, ethanol, ethylene glycol, propanol, pentanol, hexanol, cyclohexanol, n-butanol, benzyl alcohol, phenylethanol glycol monomethyl ether, glycerol, octadecene and n-octane.

[0106] In one of the embodiments, the mass fraction of the nanomaterial is 0.1%-20.0%; the mass fraction of the organic solvent is 80.0%-99.9%.

[0107] The ink adopts the above-mentioned nanomaterial, has better stability, can prolong the storage time in the printer, reduce the frequency of ink replacement, and is beneficial to industrial production.

[0108] For further information, please refer to Figure 1 As shown, the present invention further provides a light-emitting device 100, comprising a first electrode layer 110, an electron transport layer 120, a light-emitting layer 130 and a second electrode layer 140 which are stacked in sequence.

[0109] The materials of the first electrode layer 110 and the second electrode layer 140 are independently selected from at least one of metal, conductive carbon material and metal oxide. The electron transport layer 120 includes the nanomaterial described in any of the above embodiments or the nanomaterial prepared by the preparation method described in any of the above embodiments, or the electron transport layer is prepared by the ink described in any of the above embodiments.

[0110] Optionally, the preparation method of the electron transport layer 120 may be a solution method, which may be a spin coating method, a printing method, an inkjet printing method, a doctor blade method, a printing method, a dip-coating method, a soaking method, a spray coating method, a roll coating method, a casting method, a slit coating method, a strip coating method, and the like.

[0111] Among them, the metal is, for example, Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg. The conductive carbon material is, for example, graphite, carbon nanotubes, graphene and carbon fiber. The metal oxide can be a doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode including one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.

[0112] The material of the light emitting layer 130 is a quantum dot light emitting material or an organic light emitting material.

[0113] The quantum dot luminescent material is, for example, at least one of a single structure quantum dot and a core-shell structure quantum dot, the material of the single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnO At least one of CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPb At least one of SSe, SnPbSeTe and SnPbSTe, the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G At least one of aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the core-shell structured quantum dots includes any one of the above-mentioned single-structured quantum dots, and the shell material of the core-shell structured quantum dots includes CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS, ZnS and at least one of the above-mentioned single-structured quantum dots.

[0114] Organic light-emitting materials include, for example, 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, anthracene derivative blue light-emitting materials, boron-nitrogen-containing blue light-emitting materials, boron-oxygen blue light-emitting materials and boron-sulfur-containing blue light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0115] In some examples, the light emitting device 100 further includes an electron injection layer 150 disposed between the first electrode layer 110 and the electron transport layer 120 .

[0116] The material of the electron injection layer 150 can be an alkali metal salt, such as LiF, NaF, CsF, Cs2CO3, etc.; it can also be a low work function metal, such as Yb, Ca, etc.

[0117] In some examples, the light emitting device 100 further includes a hole functional layer disposed between the light emitting layer 130 and the second electrode layer 140. The hole functional layer includes a hole transport layer 160 and / or a hole injection layer 170. When the hole functional layer includes the hole transport layer 160 and the hole injection layer 170, the hole injection layer 170 is disposed between the hole transport layer 160 and the second electrode layer 140.

[0118] The material of the hole injection layer 170 can be a conductive polymer, such as PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid)); it can also be a high work function n-type semiconductor, such as HAT-CN (2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene), MoO3, WO3, V2O5, Rb2O, etc.

[0119] The material of the hole transport layer 160 can be an inorganic semiconductor, such as NiO, Cu2O, etc.; it can also be an organic semiconductor, such as: NPB (N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine), TCTA (4,4',4'-tri(carbazole-9-yl) triphenylamine), poly-TPD (poly[bis(4-phenyl)(4-butylphenyl)amine]), 3TPYMB (tri[2,4,6-trimethyl-3-(3-pyridyl)phenyl]borane), TFB (1,2,4,5-tetrakis(trifluoromethyl)benzene), TAPC (4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline]), CBP (4,4'-di(9-carbazole)biphenyl), PFB (cross-linked TFB), etc.

[0120] It can be understood that the light emitting device 100 further includes a substrate 180 , and the substrate 180 can be made of a rigid material, such as glass, or a flexible material, such as polyimide, polynorbornene, and the like.

[0121] Furthermore, an embodiment of the present application also provides a display device, which includes a light-emitting device 100 .

[0122] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0123] The following specific examples are provided to further illustrate the present invention.

[0124] Example 1

[0125] The preparation method of the nano material of this embodiment comprises the following steps:

[0126] Dissolve zinc acetate in DMF to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve sodium methoxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L.

[0127] Dissolve in ethanol to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at -20°C for 5 hours.

[0128] Example 2

[0129] The preparation method of the nano material of this embodiment comprises the following steps:

[0130] Dissolve zinc borate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve sodium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve tetrakis(trimethylsilyl)silane in n-hexane to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 7:1:0.1 and react at 40°C for 1 hour.

[0131] Example 3

[0132] The preparation method of the nano material of this embodiment comprises the following steps:

[0133] Dissolve zinc borate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve sodium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve cupric chloride in ethanol to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 7:1:0.05 and react at 40°C for 1 hour.

[0134] Example 4

[0135] The preparation method of the nano material of this embodiment comprises the following steps:

[0136] Dissolve zinc ethoxide in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in DMSO to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve nickel bromide in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 130°C for 15 minutes.

[0137] Example 5

[0138] The preparation method of the nano material of this embodiment comprises the following steps:

[0139] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium fluoride in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.5 and react at 40°C for 1 hour.

[0140] Example 6

[0141] The preparation method of the nano material of this embodiment comprises the following steps:

[0142] Dissolve zinc acetate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethylene glycol monomethyl ether to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 70°C for 3 hours.

[0143] Example 7

[0144] The preparation method of the nano material of this embodiment comprises the following steps:

[0145] Dissolve zinc alanine in ethanol to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve barium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve cuprous acetate in DMI to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:2:0.05 and react at 40°C for 1 hour.

[0146] Example 8

[0147] The preparation method of the nano material of this embodiment comprises the following steps:

[0148] Dissolve zinc ethoxide in ethanol to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve potassium tert-butoxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve zirconium acetate in DMF to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at -20°C for 5 hours.

[0149] Example 9

[0150] The preparation method of the nano material of this embodiment comprises the following steps:

[0151] Dissolve zinc chloride in ethylene glycol monomethyl ether to prepare a Zn source precursor solution a with a concentration of 0.1 mol / L. Dissolve lithium acetate in ethylene glycol monomethyl ether to prepare an alkali source precursor solution b with a concentration of 0.1 mol / L. Dissolve nickel fluoride in DMF to prepare a stabilizer solution c with a concentration of 0.03 mol / L. Mix solutions a, b, and c in a volume ratio of 1:8:0.05 and react at 80°C for 15 minutes.

[0152] Example 10

[0153] The preparation method of the nano material of this embodiment comprises the following steps:

[0154] Dissolve zinc acetate in DMF to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve barium hydroxide in ethylene glycol monomethyl ether to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMF to prepare a stabilizer solution c with a concentration of 0.006 mol / L. Mix solutions a, b, and c in a volume ratio of 1:5:0.05 and react at 80°C for 15 minutes.

[0155] Embodiment 11

[0156] The preparation method of the nano material of this embodiment comprises the following steps:

[0157] Dissolve zinc glycinate in DMF to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve ammonia water in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve titanium n-propoxide in ethanol to prepare a stabilizer solution c with a concentration of 0.006 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 40°C for 1 hour.

[0158] Example 12

[0159] The preparation method of the nano material of this embodiment comprises the following steps:

[0160] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve LiOH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve methyl orthosilicate in n-octadecane to prepare a stabilizer solution c with a concentration of 0.003 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 70°C for 15 minutes.

[0161] Example 13

[0162] The preparation method of the nano material of this embodiment comprises the following steps:

[0163] Dissolve zinc borate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve sodium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve copper fluoride in DMF to prepare a stabilizer solution c with a concentration of 0.006 mol / L. Mix solutions a, b, and c in a volume ratio of 9:1:0.05 and react at 40°C for 1 hour.

[0164] Embodiment 14

[0165] The preparation method of the nano material of this embodiment comprises the following steps:

[0166] Dissolve zinc methoxide in ethanol to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve sodium acetate in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.006 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 40°C for 1 hour.

[0167] Embodiment 15

[0168] The preparation method of the nano material of this embodiment comprises the following steps:

[0169] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium fluoride in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 20°C for 10 hours.

[0170] Example 16

[0171] The preparation method of the nano material of this embodiment comprises the following steps:

[0172] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 20°C for 50 hours.

[0173] Embodiment 17

[0174] The preparation method of the nano material of this embodiment comprises the following steps:

[0175] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 20°C for 100 hours.

[0176] Embodiment 18

[0177] The preparation method of the nano material of this embodiment comprises the following steps:

[0178] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 20°C for 150 hours.

[0179] Embodiment 19

[0180] The preparation method of the nano material of this embodiment comprises the following steps:

[0181] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 20°C for 200 hours.

[0182] Embodiment 20

[0183] The preparation method of the nano material of this embodiment comprises the following steps:

[0184] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve lithium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve lithium acetate and methyl orthosilicate in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L, wherein the molar ratio of lithium acetate to methyl orthosilicate is 1.5:1. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 70°C for 15 minutes.

[0185] Embodiment 21

[0186] The preparation method of the nano material of this embodiment comprises the following steps:

[0187] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.03 mol / L. Dissolve lithium hydroxide in ethanol to prepare an alkali source precursor solution b with a concentration of 0.03 mol / L. Dissolve 3-aminopropyltriethoxysilane and lithium fluoride in DMSO to prepare a stabilizer solution c with a concentration of 0.005 mol / L, wherein the molar ratio of 3-aminopropyltriethoxysilane to lithium fluoride is 1:1.5. Mix solutions a, b, and c in a volume ratio of 1:1:0.05 and react at 75°C for 15 minutes.

[0188] Comparative Example 1

[0189] The preparation method of the nano material of this embodiment comprises the following steps:

[0190] Dissolve zinc acetate dihydrate in DMSO to prepare a Zn source precursor solution a with a concentration of 0.3 mol / L. Dissolve TMAH in ethanol to prepare an alkali source precursor solution b with a concentration of 0.3 mol / L. Mix solution a and solution b evenly and react at 20°C for 1 hour.

[0191] The nanomaterials prepared in the above examples and comparative examples were tested, and the number of days it took for the DLS particle size to reach 150% of its initial DLS particle size was recorded as the ink stabilization time to judge its stability. The results are shown in Table 1.

[0192] Table 1

[0193]

[0194]

[0195] As can be seen from the results in Table 1, in Examples 1 to 21, ionic stabilizers and organosilicon stabilizers are added to the zinc source precursor and the alkali source precursor for reaction. Compared with the nanomaterials synthesized by the traditional method, the reaction speed at room temperature is slower, which can slow down the aggregation of particles and effectively improve the stability. As can be seen from Examples 15 to 19, when the reaction time is extended to more than 100 hours, the stability is better than that of the nanomaterials with a reaction time of less than 100 hours. As can be seen from Examples 20 to 21, when the ionic stabilizer and the organosilicon stabilizer are combined and doped, the stability of the nanomaterial is better.

[0196] It can be seen that the present application increases the reaction barrier of the reactant system by doping with a stabilizer and increasing the reaction temperature, extending the reaction time, etc. during the preparation process, so that the prepared nanomaterial continues to react more slowly at room temperature than the nanomaterial synthesized by the traditional method, which can slow down the aggregation of particles and thus improve its stability.

[0197] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0198] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A nanomaterial, characterized in that: The invention comprises ZnO nanoparticles and a stabilizer doped in the ZnO nanoparticles; The stabilizer includes at least one of an ion stabilizer and an organosilicon stabilizer.

2. The nanomaterial according to claim 1, characterized in that The molar ratio of the Zn element content in the ZnO nanoparticles to the stabilizer is (0.1-10000):1; and / or The molecular weight of the organosilicon stabilizer is less than 10,000.

3. The nanomaterial according to claim 1, characterized in that The ion stabilizer comprises at least one of fluoride ions, lithium ions, boron ions, nickel ions, zirconium ions, titanium ions, cuprous ions and cupric ions; and / or The organosilicon stabilizer is selected from at least one of the compounds represented by formula (I) to formula (V): R1-R4 are independently selected from C1-C 10 alkyl; R5-R 10 Independently selected from -H, -D, phenyl, C1-C 10 Alkyl, C1-C 10 Alkoxy; R 11 -R 13 Independently selected from C1-C 10 Alkyl, phenyl, trimethylsilyl; R 14 Selected from halogen atoms, hydroxyl groups, C1-C 10 Alkyl, imidazole, trimethylsilyl, -A1-COO-A2, wherein A1 and A2 are independently selected from C1-C 10 alkyl; R 15 -R 20 Independently C1-C 10 alkyl; R 21 Independently selected from C1-C 10 alkyl.

4. The nanomaterial according to claim 3, characterized in that The organosilicon stabilizer is selected from at least one of methyl orthosilicate, tetraacetic silicon, ethyl silicate, hexamethoxydisiloxane, hexaphenyldisiloxane, hexamethyldisiloxane, pentamethyldisiloxane, tri(trimethylsilyl)chlorosilane, tetra(trimethylsilyl)silane, trimethylsilylimidazole, ethyl trimethylsilyl acetate, 2-(trimethylsilyl)ethanol, triphenylsilanol and hexamethyldisiloxane urea.

5. The nanomaterial according to claim 1, characterized in that The stabilizer includes an ionic stabilizer and an organosilicon stabilizer; and / or The molar ratio of the ionic stabilizer to the organosilicon stabilizer is (1-5):(1-5).

6. A method for preparing a nanomaterial, characterized in that: The following steps are involved: Providing a Zn source precursor solution, an alkali source precursor solution and a stabilizer solution; The Zn source precursor solution, the alkali source precursor solution and the stabilizer solution are mixed and reacted to obtain the nanomaterial; The stabilizer solution includes at least one of an ionic stabilizer precursor and an organosilicon stabilizer.

7. The method for preparing the nanomaterial according to claim 6, characterized in that: The Zn source precursor solution includes a Zn source precursor, and the alkali source precursor solution includes an alkali source precursor; The molar ratio of the Zn source precursor to the stabilizer is (0.1-100):1, and the molar ratio of the Zn source precursor to the alkali source precursor is (0.1-10):1; and / or, The ion stabilizer precursor includes at least one of a fluoride salt, a lithium salt, a boron salt, a nickel salt, a zirconium salt, a titanium salt and a copper salt; and / or, The molecular weight of the organosilicon stabilizer is less than 10,000.

8. The method for preparing the nanomaterial according to claim 7, characterized in that: The ion stabilizer precursor meets at least one of the following characteristics: (1) The fluoride salt is at least one selected from ammonium fluoride, aluminum fluoride, strontium fluoride and zirconium fluoride; (2) The lithium salt is at least one selected from lithium chloride, lithium fluoride, lithium acetate, lithium phosphate, lithium methoxide and lithium benzoate; (3) The boron salt is selected from at least one of boron chloride, boron fluoride and boron tribromide; (4) The nickel salt is at least one selected from nickel chloride, nickel fluoride, nickel bromide and nickel iodide; (5) The zirconium salt is at least one selected from zirconium chloride, zirconium boride, zirconium bromide and zirconium acetate; (6) The titanium salt is at least one selected from titanium chloride, titanium bromide, titanium tetrafluoride and titanium n-propoxide; (7) The copper salt is selected from at least one of cuprous acetate, cuprous sulfide, cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride and cupric fluoride.

9. The method for preparing a nanomaterial according to claim 7, characterized in that: The Zn source precursor is selected from at least one of zinc carboxylate, zinc alcohol, zinc amino acid, zinc chloride, zinc nitrate, zinc bromide, zinc borate and basic zinc carbonate; and / or The alkaline source precursor is selected from at least one of alkali metal hydroxides, alkaline earth metal hydroxides, and Lewis bases; the alkali metal hydroxide is selected from at least one of lithium hydroxide and sodium hydroxide; the alkaline earth metal hydroxide is barium hydroxide; the Lewis base is at least one of ammonia water, tetramethylammonium hydroxide, lithium acetate, sodium acetate, sodium methoxide, potassium tert-butoxide, alkyl lithium, and Grignard reagent; and / or The Zn source precursor solution also includes a first solvent, the alkali source precursor solution also includes a second solvent, and the stabilizer solution also includes a third solvent, and the first solvent, the second solvent and the third solvent are independently selected from at least one of DMSO, DMF, NMF, NMP, methanol, ethanol, ethylene glycol monomethyl ether, glycerol, water, octadecene and n-octane.

10. The method for preparing a nanomaterial according to claim 6, characterized in that: The concentration of the Zn source precursor solution is 0.01 mol / L to 3 mol / L; and / or, the concentration of the alkali source precursor solution is 0.01 mol / L to 3 mol / L; and / or, the concentration of the stabilizer solution is 0.01 mol / L to 3 mol / L.

11. The method for preparing a nanomaterial according to any one of claims 6 to 10, characterized in that: The reaction is carried out at -20°C to 130°C, and the reaction time is 10 minutes to 960 hours; and / or the reaction time is 10 hours to 200 hours.

12. An ink, characterized in that: The invention comprises an organic solvent and the nanomaterial according to any one of claims 1 to 5 or a nanomaterial prepared by the preparation method according to any one of claims 6 to 11.

13. The ink according to claim 12, characterized in that: The organic solvent includes: at least one of a polar solvent, a saturated hydrocarbon solvent, an unsaturated hydrocarbon solvent, an alcohol solvent, an ether solvent, and a ketone solvent; and / or The organic solvent includes DMSO, DMF, NMF, NMP, methanol, ethanol, ethylene glycol, propanol, pentanol, hexanol, cyclohexanol, n-butanol, benzyl alcohol, phenylethanol glycol monomethyl ether, glycerol, octadecene and n-octane; and / or The mass fraction of the nano material is 0.1%-20.0%; the mass fraction of the organic solvent is 80.0%-99.9%.

14. A light emitting device, characterized in that: It comprises a first electrode layer, an electron transport layer, a light-emitting layer and a second electrode layer which are stacked in sequence; the electron transport layer comprises the nanomaterial according to any one of claims 1 to 5 or a nanomaterial prepared by the preparation method according to any one of claims 6 to 11, or the electron transport layer is prepared by the ink according to any one of claims 12 to 13.

15. The light emitting device according to claim 14, characterized in that: The light emitting device meets at least one of the following characteristics: (1) The materials of the first electrode layer and the second electrode layer are independently selected from at least one of metals, metal oxides and conductive carbon materials; (2) The material of the light-emitting layer is a quantum dot light-emitting material or an organic light-emitting material.

16. A display device, characterized in that: Comprising the light emitting device according to claim 14 or 15.